2010
DOI: 10.1007/s00415-010-5716-z
|View full text |Cite
|
Sign up to set email alerts
|

Has drug therapy changed the natural history of Parkinson’s disease?

Abstract: This narrative review examines the effects of drug therapy on the natural history of Parkinson's disease. In terms of modifying the underlying disease process, it is possible that immediate therapy, rather than deferred treatment, can have a positive effect on the underlying disease process. However, it is unlikely that drug therapy has changed mortality from the condition and there is no evidence that it can delay the onset of non-motor features such as dementia and falls. The beneficial effects of drug thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Rocha and colleagues reported that the mortality rate was 9 times higher for men than women who underwent DBS, but gender was not a predictor of death, whereas Ngoga and colleagues found that women had a higher risk of mortality than men in both DBS and medical groups. Clarke has reported that appropriate medication management for PD patients did not extend life expectancy. DBS provides many of the same benefits as medication, including reduction/elimination of tremors and rigidity and improved motor functioning, cardinal symptoms of PD .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rocha and colleagues reported that the mortality rate was 9 times higher for men than women who underwent DBS, but gender was not a predictor of death, whereas Ngoga and colleagues found that women had a higher risk of mortality than men in both DBS and medical groups. Clarke has reported that appropriate medication management for PD patients did not extend life expectancy. DBS provides many of the same benefits as medication, including reduction/elimination of tremors and rigidity and improved motor functioning, cardinal symptoms of PD .…”
Section: Discussionmentioning
confidence: 99%
“…Despite having an older cohort than is reported typically, we identified a modest survival advantage for those individuals who received DBS when compared with matched patients with PD who did not receive DBS. In contrast, medication management has not been demonstrated to provide a survival advantage . Whether the advantageous effect of DBS on survival may suggest a disease modifying effect or a moderating influence on PD comorbidities that might shorten life or is a function of unobserved differences is a question that would be best answered in a prospective longitudinal study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Life expectancy is decreased in Parkinson disease (odds ratio 2.56, i.e., the mortality risk is 2.56 times higher than similar age-matched people without Parkinson disease), and medical treatments do not appear to alter mortality or delay the onset of nonmotor symptoms. 114 Although progression is slower in patients with early-onset disease and there is longer absolute survival, this comes at the expense of increased years of life lost (11 yr lost in early-onset disease v. 4 yr in late-onset disease). 24,115 Late-onset Parkinson disease is associated with more rapid disease progression and cognitive decline, 116 which may be related to a lack of compensatory strategies against cell death.…”
Section: What Is the Prognosis?mentioning
confidence: 99%
“…So far, while drug therapies in some studies have shown a positive influence on the disease when started early on, they have not yet shown any change in mortality or the ability to prevent the onset of dementia or falls [55]. On the other hand, a trial exploring this question demonstrated that patients who underwent bilateral STN-DBS had significantly longer survival and were also significantly less likely to be admitted in a residential care facility (6%) as compared to matched patients (15%) who, while eligible for DBS, opted to be managed medically [49].…”
Section: Comparison Of the Target Sitesmentioning
confidence: 99%